Molecular dynamics simulations reveal the parallel stranded d(GGGA)3GGG DNA quadruplex folds via multiple paths from a coil-like ensemble - Pokorná, Pavlína; Mlýnský, Vojtěch; Bussi, Giovanni; Šponer, Jiří; Stadlbauer, Petr (International journal of biological macromolecules, 2024)
G-quadruplexes (G4s) are non-canonical nucleic acid structures that fold through complex processes. Characterization of the G4 folding landscape may help to elucidate biological roles of G4s but is challenging both experimentally and computationally. Here, we achieved complete folding of a three-quartet parallel DNA G4 with (GGGA)3GGG sequence using all-atom explicit-solvent enhanced-sampling molecular dynamics (MD) simulations. The simulations suggested early formation of guanine stacks in the G-tracts, which behave as semi-rigid blocks in the folding process. The folding continues via the formation of a collapsed compact coil-like ensemble. Structuring of the G4 from the coil then proceeds via various cross-like, hairpin, slip-stranded and two-quartet ensembles and can bypass the G-triplex structure. Folding of the parallel G4 does not appear to involve any salient intermediates and is a multi-pathway process. We also carried out an extended set of simulations of parallel G-hairpins. While parallel G-hairpins are extremely unstable when isolated, they are more stable inside the coil structure. On the methodology side, we show that the AMBER DNA force field predicts the folded G4 to be less stable than the unfolded ensemble, uncovering substantial force-field issues. Overall, we provide unique atomistic insights into the folding landscape of parallel-stranded G4 but also reveal limitations of current state-of-the-art MD techniques.
Keywords: Nucleic Acids; DNA; simulace molekulární dynamiky; G-kvadruplexy; Folding; Nucleic Acid Conformation; nukleové kyseliny; Molecular dynamics; Molecular Dynamics Simulation; G-Quadruplex; G-Quadruplexes; konformace nukleové kyseliny